Do efficient banking sectors accelerate economic growth in transition countries? - Tuuli Koivu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
The relationship between financial sector and economic growth in transition countries has been largely ignored in the earlier empirical literature.In this paper, we analyse the finance-growth nexus using a fixed-effects panel model and unbalanced panel data from 25 transition countries during the period 1993-2000.We measure the qualitative development in the banking sectors using the margin between lending and deposit interest rates.Our second variable for the level of financial sector development is the amount of bank credit allocated to the private sector as a share of GDP.According to our results, the interest rate margin is significantly and negatively related to economic growth.This outcome is in line with theoretical models and has important policy implications.On the other hand, a rise in the amount of credit does not seem to accelerate economic growth.The main reasons behind this result could be the numerous banking crises the transition countries have experienced and the soft budget constraints that are still prevalent in many transition countries. Due to these specific characteristics the growth in credit has not always been sustainable and in some cases it may have led to a decline in growth rates.
URN:NBN:fi:bof-201408071978
Keywords: 330; financial sector; transition economies; economic growth; panel data